GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MARANTHA KREASINDO MEDAN - Nikous Soter Sihombing; Amril Amril; Lasman Eddy Bachtiar; Arisman Parhusip; Montaris Silaen (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Employee performance is the result of work in quantity and quality achieved by employees in carrying out their duties in accordance with the responsibilities given. Companies need to improve employee performance such as improving leadership styles, providing good motivation and increasing employee work discipline. Leadership style is a form of behavior that can be made to integrate group goals with individual goals. Motivation is the thing that causes, distributes and supports human behavior so that they want to work hard and enthusiastically achieve optimal results. Work discipline is a tool used by managers to communicate with their employees so that they are willing to change a behavior as well as an effort to increase one's awareness and willingness to obey all company regulations or applicable social norms. Employee performance is the work achieved by an individual that is adjusted to the role and task of the individual in a company at a certain time period associated with a certain standard value measure of the company where the individual works. The purpose of this study was to determine and analyze the influence of leadership style, motivation and work discipline on the performance of employees of PT. Marantha Kreasindo Medan. This research was conducted at PT. Marantha Kreasindo Medan. The type of research used is descriptive quantitative research. The results of the study simultaneously show that the variables of leadership style, motivation and work discipline have a positive and significant effect on employee performance. Partially, the leadership style and work discipline variables have no significant effect on employee performance, while the motivation variable has a significant effect on employee performance.